The Policy Authority of Police in Implementing Rehabilitation Actions ont Narcotics Users - Muhammat Teguh Safi'i; Jawade Hafidz; Maryanto Maryanto (Universitas Islam Sultan Agung, 2022)
The purpose of this research is to analyze the police authority policy in the implementation of rehabilitation measures against narcotics users in the current positive law and to analyze the narcotics authority policy in the future positive law. This study used a sociological juridical approach, with a qualitative descriptive research method. The research problem was analyzed using the theory of justice and the theory of the operation of law. The results of the study conclude that 1) Law enforcement of rehabilitation sanctions against narcotics users currently begins when the police conduct investigations and investigations by looking at the criminal provisions of Article 127 paragraphs (2) and (3) so that there is consistency in paying attention to the Articles that regulate the provisions so that Later the addicts and victims of narcotics abusers can be rehabilitated both in rehabilitation and no longer sentenced to prison or imprisonment because the rehabilitation is counted as a period of serving the sentence. 2) In the future positive law formulation, is needed that is built on an integrated and harmonious investigation coordination and supervision system but does not have multiple interpretations so that there is no overlapping investigative authority caused by the arrangements and legislation formulations in positive legal provisions such as the current and current cases. Narcotics abuse can not be handled appropriately.